Development and Validation of Diagnostic Instrument to Identify Student Misconceptions in Vector Material - Firdaus, Arrafikar Rizqia; Wulandarie, Elza; Cantika, Mira; Suryana, Tresna Galih Sukma (Journal of Innovative Physics Education Research, 2025)
This study aims to develop and validate a web-based diagnostic instrument to detect students' misconceptions on vector material, including the concepts of vector magnitude, vector components, resultant, and vector displacement. The research was conducted using a quantitative research design, involving 30 students of class XI IPA 3 SMA Negeri 1 Padarincang. The research process includes instrument development, expert validation, limited trial, and data analysis. The results showed that the instrument had adequate reliability and validity, with KR-20 reliability of 0.848 (high category). The instrument is effective in identifying misconceptions, especially on the concepts of resultant and vector displacement. This article contributes to the development of diagnostic-based physics learning evaluation.